2020
DOI: 10.3389/fgene.2020.602542
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of lncRNA-Mediated ceRNA Network Reveals a Prognostic Signature for Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of malignancy and is associated with high mortality. Prior research suggests that long non-coding RNAs (lncRNAs) play a crucial role in the development of HCC. Therefore, it is necessary to identify lncRNA-associated therapeutic biomarkers to improve the accuracy of HCC prognosis. Transcriptomic data of HCC obtained from The Cancer Genome Atlas (TCGA) database were used in the present study. Differentially expressed RNAs (DERNAs), including 74 lncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Recent studies set up several prognostic risk models with lncRNAs aimed at predicting the prognosis of patients with HCC via bioinformatics analysis ( 17 , 18 , 41 ). These papers demonstrated the potential clinical value of lncRNAs for predicting HCC patients’ OS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies set up several prognostic risk models with lncRNAs aimed at predicting the prognosis of patients with HCC via bioinformatics analysis ( 17 , 18 , 41 ). These papers demonstrated the potential clinical value of lncRNAs for predicting HCC patients’ OS.…”
Section: Discussionmentioning
confidence: 99%
“…The ceRNA network of HOXD-AS1/miR-130a-3p/SOX4 as well as CASC2/miR-367/FBXW7 may play a prometastatic role in HCC ( 15 , 16 ). Moreover, several ceRNA networks have been screened as prognostic signatures for HCC, but further experiments to validate these networks are needed in these studies ( 17 , 18 ). Most importantly, few studies have reported the relationship among the ceRNA network, TMB and immune infiltration in HCC.…”
Section: Introductionmentioning
confidence: 99%
“… 31 A previous lncRNA signature containing MIR137HG was also reported to be a reliable prognostic model for HCC patients. 32 ZNF295-AS1 was also reported to be highly expressed in human epithelial ovarian cancer via microarrays and RT-qPCR. 33 To date, few studies have investigated the correlation of these lncRNAs with gefitinib resistance.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, a large number of previous studies have explored the lncRNA/miRNA/mRNA ceRNA network in HCC [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In contrast to these studies, the present study is the first to investigate the lncRNA/miRNA/mRNA ceRNA network in HCV-related HCC, and the network was associated with patient prognosis.…”
Section: Discussionmentioning
confidence: 99%